Primary sarcopenia is associated with elevated spontaneous NET formation - Balazs, Irina; Stelzer, Manuel; Traub, Julia; Horvath, Angela; Feldbacher, Nicole; Stadlbauer, Vanessa (Frontiers in Cell and Developmental Biology, 2024)
Introduction. Sarcopenia is a frequent complication of liver cirrhosis, but it can also occur independently from any underlying cause. Neutrophil function, including neutrophil extracellular trap (NET) formation, is linked to chronic inflammation, however, has not been extensively studied in patients with sarcopenia. Here we aim to study if main neutrophil functions are altered in patients with sarcopenia with or without liver cirrhosis. Methods. Neutrophils from 92 patients (52 patients with liver cirrhosis and sarcopenia, 25 patients with liver cirrhosis without sarcopenia and 15 patients with sarcopenia without liver cirrhosis), as well as 10 healthy controls were isolated and stimulated with heat-inactivated E. coli (250 bacteria/cell), phorbol 12-myristate 13-acetate (PMA) (100nM) or incubation medium in duplicates for 2 hours at 37°C. Cells were fixed with paraformaldehyde and stained with 4′,6-diamidino-2-phenylindole (DAPI). Pictures of 10 random fields of vision per slide were taken with Olympus BX51 Fluorescence Microscope (Olympus, Shinjuku, Tokyo, Japan) at 600x total magnification. DNA Area and NETosis Analysis (DANA) algorithm was used to quantify the percentage of NET formation per patient. Phagocytosis and ROS production were assessed with PhagotestTM kit and PhagoburstTM kit. Results. Spontaneous NET formation was significantly elevated in patients with only sarcopenia compared to patients with cirrhosis and sarcopenia (p=0.008) and healthy controls (p=0.039). NET formation in response to PMA was significantly decreased in patients with cirrhosis (p=0.007), cirrhosis and sarcopenia (p<0.001), sarcopenia (p=0.002) compared to healthy controls. There was no significant difference in NET formation in response to E. coli between the groups. DANA algorithm was successfully optimized and validated for assessment of clinical samples. There were no significant changes in neutrophil phagocytosis between patients’ groups and compared to healthy controls. There was significantly lower percentage of neutrophils producing ROS in response to fMLF in patients compared to healthy controls. Discussion. Spontaneous NET formation might contribute to chronic inflammation and primary sarcopenia pathogenesis. The semi-automated NET formation analysis can be successfully implemented to analyse vast amount of data generated within clinical studies. Further research is needed to explore the mechanism of NET formation in patients with sarcopenia and its potential as a biomarker in sarcopenia.